Patient and surgeon predictors of achieving the critical view of safety in laparoscopic cholecystectomy: a prospective cohort study - Addasi, Rami; Al-Sabe’, Lana; AlRawabdeh, Kareem; Abu-Zayed, Rand; Alaarag, Abdallah; Ribeiro, Marcelo A. F.; Helmy, Ahmed H.; El Muhtaseb, M. S.; Daradkeh, Salam (Frontiers in Surgery, 2025)
IntroductionThe Critical View of Safety (CVS) is a cornerstone of safe laparoscopic cholecystectomy (LC), aimed at minimizing the risk of bile duct injury (BDI). However, consistent achievement of CVS remains a challenge in surgical practice. The primary outcome of this study was to assess the rate of CVS achievement and to identify patient, disease and surgeon related predictors.MethodsA prospective cohort of 150 patients undergoing LC was analyzed. Demographic data, preoperative risk factors, intraoperative variables, and surgeon characteristics were examined. CVS assessment was performed using Strasberg's criteria. Binary logistic regression and Chi-squared test were used to identify independent predictors of CVS achievement.ResultsThe rate of CVS achievement in this study was 69.6% among consultants and 60.0% among residents. Logistic regression identified ASA grade I (p = 0.031), emergency surgery (p = 0.01), acute cholecystitis (p = 0.031), and non-HPB surgeons (p < 0.001) were associated with higher rate of CVS achievement. The higher rate of CVS achievement among non-HPB surgeons may reflect differences in case complexity, documentation practices & stricter adherence to protocols. Other factors including level of surgeon experience, Tokyo severity grade, intraoperative Nassar difficulty grading scale, age, male gender, BMI, diabetes mellitus and clinical frailty score were not significant. There were zero cases of bile duct injury in this study, precluding analysis of CVS failure impact on BDI.ConclusionBoth preoperative and intraoperative factors can influence a surgeon's ability to achieve CVS. In our study, lower ASA grade, emergency cholecystectomies, acute cholecystitis and operations performed by non-HPB surgeons were associated with a higher likelihood of achieving CVS. Standardized protocols and structured training may help improve CVS documentation across practice settings.